PREDICTABILITY STUDY OF GROUND WATER MODELING FOR DEWATERING IN THE DEEP MILL LEVEL ZONE BLOCK CAVE - Rinaldi, Nanda
Block cave mine operations with mine locations below the groundwater table will always be affected by groundwater flow. In certain circumstances, block cave Mine operations will consider dewatering to reduce the amount of ‘passive inflow’ or seepage flow that will enter the extraction level operation area. Mine planning usually involves groundwater modeling and simulation to assess the amount of flow that will infiltrate into the extraction zone. Since around 1997 during block cave Mine operations in the Eastern Erstberg Skarn System (EESS) area with GBT/IOZ-DOZ-DMLZ collapse mines, PT. Freeport Indonesia has developed groundwater modeling using MineDW software to estimate seepage flow to the extraction level zone, however, the modeling carried out often does not include simulations of the planned dewatering that will be carried out. Modeling is more directed in estimating the passive inflow that will be obtained at the extraction level due to water seepage from the saturated zone around the collapsed zone. While the estimation of the scale of the dewatering flow is more based on the premise that "to achieve a state where the seepage flow to the extraction level decreases close to the estimated recharge value in the area of a block cave mine footprint, a drain flow from the surrounding mine footprint will be required that is greater than the estimated seepage to the extraction level which is estimated to never be achieved by a dewatering efforts". This thesis will present the results of modeling simulations to estimate the passive inflow to the extraction level of the DMLZ mine using a regional model that has been developed in 2017 input with newer plan of DMLZ and back-simulating the dewatering required by the DMLZ Block Cave Mine in the mine plan step and comparing it with the dewatering drain flow obtained after 10 years of dewatering drilling since 2014.